Search code examples
javaloopsfor-loopinfinite-looppost-increment

Post increment operator not incrementing in for loop


I'm doing some research about Java and find this very confusing:

for (int i = 0; i < 10; i = i++) {
  System.err.print("hoo... ");
}

This is never ending loop!

Anybody has good explanation why such thing happens?


Solution

  • for (int i = 0; i < 10; i = i++) {
    

    The above loop is essentially the same as: -

    for (int i = 0; i < 10; i = i) {
    

    the 3rd part of your for statement - i = i++, is evaluated as: -

    int oldValue = i; 
    i = i + 1;
    i = oldValue;  // 3rd Step 
    

    You need to remove the assignment from there, to make it work: -

    for (int i = 0; i < 10; i++) {
    

    (On OP request from Comments)

    Behaviour of x = 1; x = x++ + x++; : -

    As far as your issue as specified in the comment is concerned, the result of the following expression: -

    x = 1; 
    x = x++ + x++;
    

    is obtained as follows: -

    Let's mark different parts of the second statement: -

    x = x++ + x++;
    R    A     B
    

    Now, first the RHS part (A + B) will be evaluated, and then the final result will be assignmed to x. So, let's move ahead.

    First A is evaluated: -

    old1 = x;  // `old1 becomes 1`
    x = x + 1; // Increment `x`. `x becomes 2`
    //x = old1; // This will not be done. As the value has not been assigned back yet.
    

    Now, since the assignment of A to R is not done here, the 3rd step is not performed.

    Now, move to B evaluation: -

    old2 = x;  // old2 becomes 2. (Since `x` is 2, from the evaluation of `A`)
    x = x + 1; // increment `x`. `x becomes 3`.
    // x = old2; // This will again not be done here.
    

    Now, to get the value of x++ + x++, we need to do the last assignment that we left in the evaluation of A and B, because now is the value being assigned in x. For that, we need to replace: -

    A --> old1
    B --> old2   // The last assignment of both the evaluation. (A and B)
    
    /** See Break up `x = old1;` towards the end, to understand how it's equivalent to `A = old1; in case of `x = x++`, considering `x++ <==> A` in this case. **/
    

    So, x = x++ + x++, becomes: -

    x = old1 + old2;
      = 1 + 2;
      = 3;  // Hence the answer
    

    Break up of 3rd part of x = x++, to see how it works in x = x++ + x++ case: -

    Wonder why the replacement is done as A --> old1 and not x --> old1, as in case of x = x++.

    Take a deep look at x = x++ part, specially the last assignment: -

    x = oldValue;
    

    if you consider x++ to be A here, then the above assignment can be broken into these steps: -

    A = oldValue;
    x = A;
    

    Now, for the current problem, it is same as: -

    A = old1;
    B = old2;
    x = A + B;
    

    I hope that makes it clear.